Follicular ameloblastoma: A case report - Shivani Singh; Kamal Hasan; Abhijeet Alok (Wolters Kluwer Medknow Publications, 2019)
Ameloblastomas are slow-growing, locally invasive tumor affecting the maxillofacial region. There are various histologic variants of ameloblastoma. Most common being follicular ameloblastoma. Follicular ameloblastoma is commonly seen in elder people. Follicular ameloblastomas have got high recurrence rate. Radiographic finding shows a multilocular radiolucency with well-defined borders. This paper presents a case of follicular ameloblastoma in a 30-year-old female who had a swelling on the right mandible region.